2016
DOI: 10.1117/1.jbo.21.8.081208
|View full text |Cite
|
Sign up to set email alerts
|

Optical clearing of skin enhanced with hyaluronic acid for increased contrast of optoacoustic imaging

Abstract: Abstract. Enhanced delivery of optical clearing agents (OCA) through skin may improve sensitivity of optical and optoacoustic (OA) methods of imaging, sensing, and monitoring. This report describes a two-step method for enhancement of light penetration through skin. Here, we demonstrate that topical application of hyaluronic acid (HA) improves skin penetration of hydrophilic and lipophilic OCA and thus enhances their performance. We examined the OC effect of 100% polyethylene and polypropylene glycols (PPGs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 73 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…Depending on the OCA, optimal clearing occurs after about 15 min [ 21 ]. Hydrophilic polyethylene glycol (PEG)-based polymers and lipophilic polypropylene glycol (PPG)-based polymers are approved by the FDA for medical applications [ 22 ]. These compounds both have a refractive index ≈1.47, close to that of dermal collagen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the OCA, optimal clearing occurs after about 15 min [ 21 ]. Hydrophilic polyethylene glycol (PEG)-based polymers and lipophilic polypropylene glycol (PPG)-based polymers are approved by the FDA for medical applications [ 22 ]. These compounds both have a refractive index ≈1.47, close to that of dermal collagen [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…198 The enhanced delivery of OCAs [PEG and polypropylene glycol (PPG)] through skin in vitro at sample pretreatment by hyaluronic acid (HA) provided a significant increase of NIR light transmittance (up to 47-fold) and improvement of OA/PA image contrast. 293 This two-step technique due to action of 0.5% HA in aqueous solution during 30 min improves skin penetration for hydrophilic and lipophilic OCAs.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%
“…1,17 Recent studies from different research groups on immersion OC at application of widely used OCAs to OA/PA systems showed great benefits expressed in much better probing depth and spatial resolution of these systems. 198,285,[286][287][288][289][290][291][292][293] First, it was demonstrated for optical resolution PA microscopy (OR-PAM) in two different modifications. 287,288 As in OR-PAM, the lateral resolution is determined by the diffraction-limited light focusing, which degrades due to light scattering, and the probing depth is limited by the photon transport mean free path, which is also in tissues determined by light scattering, suppression of scattering at tissue interaction with an OCA strongly improves these characteristics of the microscope.…”
Section: Wavefront Shaping and Computational Tissue Optical Clearingmentioning
confidence: 99%
“…However, topical applications of optical clearing agents are rendered ineffective owing to the stratum corneum functioning as a barrier, preventing optical clearing agents from reaching the dermis (Zhu et al, 2013). To overcome this, physical methods such as tape stripping to remove the stratum corneum or chemical penetration enhancers such as the application of thiazone (Zhu et al, 2013) or hyaluronic acid (Liopo et al, 2016) could potentially improve optical clearing agent permeation into the dermis. Alternatively, a dermal injection can be used, but the concentration of optical clearing agents is still an issue; too low and skin will not be sufficiently cleared, and too high and problems such as necrosis (Mao et al, 2009) or blood vessel occlusions can occur (Vargas et al, 2003).…”
Section: Limitationsmentioning
confidence: 99%